Analisis Pengetahuan Wajib Pajak Umkm Pasca Diberlakukannya Peraturan Pemerintah Nomor 55 Tahun 2022 Di Wilayah Kota Bekasi - Sandy, Sephia Permata Ari; Hidayati, Mainita (Jurnal Ilmu Administrasi Publik, 2024)
The research addresses the limited understanding of taxation among micro, small, and medium enterprises (MSMEs) in Bekasi City area, Indonesia, particularly regarding Government Regulation Number 55 of 2022, which introduces a 0,5% final income tax. Its objective is to assess the level of tax knowledge among MSME taxpayers’ post-implementation of PP Number 55 of 2022. Employing descriptive qualitative research methods, data collection involved observation, interviews, and documentation. It took palce at the Bekasi City Coorpratives and SMEs servise. Findings indicate that MSME taxpayers’ awareness remains deficient following the enactment of Government Regulation No. 55 of 2022. Suboptimal implementation attributed to insufficient outeach to business actors persists, and the regulation continues to burden MSMEs, leading to financial losses.